Digital human modeling third International Conference, ICDHM 2011, held as Part of HCI International 2011, Orlando, FL, USA July 9-14, 2011, Proceedings - International Conference on Digital Human Modeling Orlando, Fla.) 2011; Duffy, Vincent G.; SpringerLink (Online service).; International Conference on Human-Computer Interaction Orlando, Fla.) 2011 (Berlin Heidelberg New York Springer, 2011)
This book constitutes the refereed proceedings of the Third International Conference on Digital Human Modeling, ICDHM 2011, held in Orlando, FL, USA in July 2011. The 58 revised papers presented were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the thematic area of anthropometry applications, posture and motion modeling, digital human modeling and design, cognitive modeling, and driver modeling.
International conference proceedings.
Electronic reproduction.
Keywords: Human body -- Computer simulation -- Congresses; Human mechanics -- Computer simulation -- Congresses; Human engineering -- Computer simulation -- Congresses; Digital computer simulation -- Congresses; Electronic books